SOME ASPECTS OF THE RESULTS OF OPERATIONAL AND INVESTIGATIVE ACTIVITIES IN THE PROCESS OF PROOF IN CRIMINAL CASES - Kairat Rysbekovich, Тусупбеков (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article contains the questions concerning materials of operational investigation in the criminal trail. Based on the foreign experience appropriate regulations in the current legislation are suggested.